Lumbar Disk Pseudotumor: An Unusual Presentation of Lumbar Spinal Fracture and Stenosis - Koenigsberg, Robert A.; Black, Perry; Faro, Scott H.; Rykken, Jeffrey (American Journal of Neuroradiology, 2002)
Summary: We present an unusual case of a primary lumbar disk-space mass that presumably developed secondary to a chronic hyperextension spinal fracture associated with spinal stenosis. This injury resulted in the appearance of a lumbar intervertebral disk-space mass or pseudotumor. The pseudotumor most likely resulted from a prior spinal fracture, leading to a fused hyperextension deformity in a patient with underlying chronic degenerative spinal disease.